Proposta de método para avaliar risco de contaminação de águas subterrâneas por pesticida com base nos métodos Gus e Drastic - Viana, Tereza Neuma Araújo de Carvalho (2014)
With the crisis of the tobacco sector in the late 90s growing vegetables in the Southwest region of the city of Arapiraca-AL became the main agricultural activity. Most olericultores cultivated in a conventional way, including the use of pesticides. These inputs are generally used without the agronomic prescription and at odds with the recommendations required by the manufacturer. The indiscriminate use of pesticides over time has Caused contamination of groundwater. The contamination of groundwater by pesticides depends on the characteristics of the environment and the contaminant. There are methodologies that analyze hydrogeological characteristics of the area and others who evaluate the leaching potential of pesticides. The application of a methodology that assesses both the hydrogeological characteristics of the region as the potential for leaching of pesticides is relevant, since it selects pesticides should be given priority and analyzed more accurately identifies the areas at greatest risk of contamination, enabling a more efficient management of water resources. Given the above this study aims to propose a methodology to assess the risk of groundwater contamination by pesticide based on the method of pesticide DRASTIC vulnerability (ALLER et al., 1987) and leaching index GUS (GUSTAFSON, 1989). To this end, we analyzed the potential for leaching of pesticides used by olericultores and hydrogeological characteristics of the Green Belt Arapiraca-AL region. The proposal includes the use of weight and the GUS index method based on the weights and indices of pesticide DRASTIC methodology as well as the grouping of both methods using Geographic Information Systems (GIS). In the study of the method of GUS pesticides that have the greatest risk of contamination of groundwater in the study area are the insecticides Connect, Confidor Ampligo and Actara. As the same method, the region has areas of low, medium to high risk of contamination. In the analysis of pesticide DRASTIC methodology region has low average and vulnerability to contamination by pesticides. After grouping the two methodologies, GUS method and DRASTIC pesticide was identified that the area of the Green Belt Arapiraca shows areas of low, medium and high potential risk of contamination of groundwater by pesticide. The areas with medium risk correspond to 10,911 hectares (93.11% of the Green Belt region). In some areas, where the study of the DRASTIC methodology presented average vulnerability to pesticide contamination of groundwater by pesticide, started presenting high risk of contamination due to the addition of a factor that has been studying the potential for leaching of pesticides.